Narcolepsy Syndrome in a Patient with Multiple Sclerosis - Deniz Yerdelen; Gülçin Benbir; Uğur Uygunoğlu; Aksel Siva; Derya Karadeniz (Türk Uyku Tıbbı Dergisi, 2014)
Narcolepsy syndrome is characterized by excessive daytime sleepiness with or without cataplexy. In addition to excessive daytime sleepiness and cataplexy, other symptoms related to REM-sleep such as disturbed night sleep, sleep paralysis and hypnopompic/hypnagogic hallucinations may accompany. In the pathophysiology of idiopathic narcolepsy syndrome, loss of hypothalamic neurons producing hypocretin (orexin) has been shown, probably secondary to an autoimmune process. Although uncommon, narcolepsy syndrome may occur secondary to other neurological disorders. In this case report, a 37-year-old female patient followed due to multiple sclerosis (MS), who developed narcolepsy syndrome is presented; on this context, we aimed to draw attention to association of MS and narcolepsy syndrome. An acute MS attack may present as narcolepsy syndrome due to hypothalamic lesions, or even when MS is not active, these patients are susceptible to develop narcolepsy syndrome probably due to shared autoimmune mechanisms.